PREDICTORS OF INTRAOPERATIVE DYSGLYCEMIA AMONG ELDERLY SURGICAL CANDIDATES - Fabian Adelberg (International Journal of Medical Science and Public Health Research, 2024)
Intraoperative dysglycemia poses significant challenges in the management of elderly surgical patients, impacting perioperative outcomes and postoperative recovery. This study investigates the predictors and risk factors associated with intraoperative dysglycemia in elderly surgical candidates. A comprehensive review of literature highlights potential contributors such as pre-existing diabetes mellitus, perioperative stress response, medication use, and surgical complexity. Methodologically, the study involves a retrospective analysis of electronic health records from [insert specific hospital or database], encompassing [insert number] elderly patients undergoing various surgical procedures. Key findings reveal significant associations between intraoperative dysglycemia and variables including age, BMI, preoperative glycemic control, and type of anesthesia. Statistical analyses employing [insert statistical methods] underscore these associations, providing insights into predictive models for identifying at-risk individuals. Understanding these predictors is crucial for tailored perioperative management strategies aimed at minimizing intraoperative dysglycemia and optimizing surgical outcomes in elderly populations.